Fatores que interferem na aceitação da alimentação via oral em pacientes hospitalizados em uma unidade de terapia intensiva adulto - Alves, Maria Julia Rodrigues (Universidade Federal de São Carlos, 2024)
To identify the factors that interfere with the acceptance of oral feeding in patients hospitalized in an Adult Intensive Care Unit. Method: Cross-sectional, descriptive and methodological study, developed at the University Hospital of the Federal University of São Carlos, with convenience sampling. Stage 1: The factors that interfere with the acceptance of oral feeding by patients in the sector were identified. Stage 2: The multidisciplinary team was asked about the factors that may influence the acceptance of oral feeding by hospitalized patients. Stage 3: Creation of a folder containing information related to the factors identified in the previous stages. Research approved under Certificate of Presentation of Ethical Appreciation No. 76766823.2.0000.5504 and by the Research Ethics Committee of the Federal University of São Carlos under opinion No. 6,721,429. Results: 26 patients participated in the study. In the "Organizational" category, 10 (38.5%) patients reported being interrupted by the team during mealtime to perform some procedure. In "Choices", not being able to choose the desired foods was mentioned by 12 (46.2%) patients. In the "Hunger" category, feeling or not feeling hungry at mealtimes was reported by 14 (53.8%) patients, and in the "Eating difficulties" category, 13 (50%) reported difficulties with packages and unwrapping food. In relation to the "Quality/satisfaction with food" category, 15 (57.5%) stated that the taste of food influences diet acceptance; in "Effects of the disease", 21 (80.8%) patients reported anxiety and 21 (80.8%) sadness as potential influencers in the eating process. A total of 42 (77.7%) professionals participated. In the "Organizational" category, 12 (26.8%) identified interruptions during feeding to perform medical and nursing procedures; in "Choices", 12 (26.1%) highlighted that the patient's food preference was not respected/individual taste; in the "Hunger" category, lack of appetite was cited by 8 (17.4%) professionals; in the "Feeding difficulties" category, the use of disposable cutlery was pointed out by 5 (10.9%) professionals; in "Quality/satisfaction with food", 11 (23.9%) reported patient dissatisfaction with the taste of food; and in the "Effects of the disease" category, 5 (10.9%) reported that nausea and vomiting can hinder patients' acceptance of food. Conclusions: this study confirms that there are factors that interfere with food intake in Intensive Care Units, and it is important to evaluate and monitor them, as well as interventions to minimize them, since they can compromise food intake during the patient's hospitalization in Intensive Care.
Factors that interfere with the acceptance of oral feeding in patients hospitalized in an adult intensive care unit
Keywords: Acesso a alimentos; Estado nutricional; Equipe multiprofissional; UTI adulto; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM MEDICO-CIRURGICA